SCIENTIFIC INITIATION WORK AT HIGH SCHOOL: DEVELOPMENT OF RESEARCH SKILLS IN DAIRY PRODUCING PROPERTIES OF VALE DO TAQUARI/RS - Claudete Rempel; Mônica Jachetti Maciel; Claus Haetinger; Patrícia Caye Bergmann; Pauline Amanda Vognach; Gustavo Rodrigo da Silva (Universidade Federal de Sergipe, 2019)
The Scientific Initiation during the High School provides the development of scientific spirit and critical world view. The present work seeks to verify the skills developed through the work in Scientific Initiation of two high school students from a state school in the municipality of Lajeado / RS. In order to do so, the students were instructed to create and apply a script of semi-structured questions to 60 dairy farmers from Vale do Taquari, participants of the research group "Sustainability in Milk Producing Properties", conducted through interviews. Afterwards, the data were tabulated and analyzed by the students, allowing conclusions and presentation of the results, also evaluating students performances. It was concluded that the students developed skills in communication, data interpretation, autonomy and resourcefulness in the search for scientific materials